How RIASEC personality traits crystallizes occupational preferences among adolescents: Match or mismatch - Samiah Ahmed; Alia Ahmed; Taseer Salahuddin (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Current Study investigated how RIASEC personality traits impact the crystallization of occupational preferences among young adolescents via theoretical lens of vocational choice theory. A sample of 1147 students ranging from 13 to 21 years was used to test RIASEC model. Results using Holland's RIASEC Scale test (1997)depicted a significant impact of RIASEC personality traits in occupational preferences. Gender appeared to be a strong determinant in variation pattern of vocational choice. Understanding these patterns can help students, parents, policy makers and academic institutions in helping young adolescents in making better career choices and in turn will direct human resource to most optimal productive path in an economy.
Keywords: 330; personality interests; occupational preferences; occupational gender segregation; RIASEC personality traits